A képzési terület és a felsőoktatási intézmény hatása a fiatal diplomások munkaerő-piaci sikerességére a 2000-es évek végén - Júlia Varga (Hungarian Academy of Sciences, Institute of Economics, 2010)
– The paper uses data from a large representative survey of Hungarian higher education graduates (DPR 2010) to study the early labour market effects of field of study and college quality. Propensity score matching average treatment effect method is used to reveal the effect of the field of study, and college fixed effects are investigated to determine the effect of college quality. Results show that graduates in economics and law earn more than they would if they had chosen some other field of study Specialization in teaching, by contrast, decreases not only earnings but employment probability as well. As regards the effect of the college of graduation, some colleges have significant positive or negative effect on either employment probability or on earnings but none on both. From among the most prestigious institutions, only Budapest University of Technology and Economics proved to have significant positive effect on after-graduation earnings.
Keywords: C14; I21; I23; J24; 330; returns to college quality; returns to field of study; propensity score matching models; Studienfach; Hochschule; Dienstleistungsqualität; Bildungsertrag; Arbeitsmarkt; Ungarn